Membranes : Materials, Simulations, and Applications - Maciel-Cerda, Alfredo (Springer International Publishing : Imprint: Springer, 2017)
This book describes current advances in the research on membranes and applications in industry, groundwater, and desalination processes. Topics range from synthesis of new polymers to preparation of membranes using new water treatments for effluents, graphite membranes, development of polymeric and ceramic materials for production of membranes intended to separate gases and liquids, and liquid-liquid phases. The authors include materials used to produce catalytic membranes for polymer synthesis. The book also details theoretical approaches and simulation of membrane processes and parameters and design. Describes application of membranes in industry, groundwater, and desalination processes Details simulation of membrane processes and parameters and design Includes ceramic membranes, graphite membranes, and theoretical approaches.- Resumé vydavatel
Keywords: membrány; nauka o materiálu; polymerní membrány; membranes; materials science; polymer membranes; elektronické knihy; sborníky; electronic books; papers of several authors